Mode of action of tocotrienol as anticancer - Widiyasri Lodu; Ferry Fredy Karwur (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Tocotrienols are fat soluble substances members of the vitamin E family with the main properties of antioxidant. They are composed of the chiral center of chromanol ring with polypreniyl side chains. Research suggests that tocotrienols have a number of health benefit, and one of them as an anticancer agent. As an anticancer, tocotrienols could perform in different processes of the multi stages of cancer development and interact with other anticancer medicines and other bioactive substances, suchs geneistein, lovastin, hydroxychavicol, 6- gingerol and sesamin. The anticancer activities occur through their roles as antioxidant, coenzyme, gene expression regulator, and preventing cholesterol synthesis by inhibiting the expression of HMGCR enzyme after transcription, through this method, tocotrienols could control the cholesterol level of cancer cells and prevent the growth of the cancer. Tocotrienols target several signalling pathways at cellular and molecular levels.